2017
DOI: 10.1080/00498254.2016.1269375
|View full text |Cite
|
Sign up to set email alerts
|

Oral pharmacokinetic interaction of ester rich fruit juices and pharmaceutical excipients with tenofovir disoproxil fumarate in male Wistar rats

Abstract: 1. The aim of this study was to evaluate the role of intestinal esterases on the absorption process of tenofovir disoproxil fumarate (TDF). 2. The esterase inhibition capacity of fruit juices (FJs) rich in ester linkages and pharmaceutical excipients (having ester bonds) was performed in vitro by incubating TDF with each FJ and excipient in the intestinal washings. The ex vivo everted gut sac model was also used to evaluate the absorption enhancement capacity of these FJs and excipients. Single-dose oral pharm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…As TDF is a substrate of Pgp, studies were done to determine whether ester-rich fruit juices increase its bioavailability and intestinal absorption. Strawberry juice extract increased TDF intestinal absorption in Caco-2 cell lines to 67%, whereas grapefruit and cranberry juice extracts increased TDF bioavailability by 97% and 24% in an in vivo rat study (Van Gelder et al, 1999;Shailender et al, 2017). Additional investigation needs to be done to determine whether this effect is also seen in humans.…”
Section: Effect Of Food Intake On Tdf Bioavailabilitymentioning
confidence: 98%
“…As TDF is a substrate of Pgp, studies were done to determine whether ester-rich fruit juices increase its bioavailability and intestinal absorption. Strawberry juice extract increased TDF intestinal absorption in Caco-2 cell lines to 67%, whereas grapefruit and cranberry juice extracts increased TDF bioavailability by 97% and 24% in an in vivo rat study (Van Gelder et al, 1999;Shailender et al, 2017). Additional investigation needs to be done to determine whether this effect is also seen in humans.…”
Section: Effect Of Food Intake On Tdf Bioavailabilitymentioning
confidence: 98%
“…Grapefruit also helps with atherosclerosis. Grapefruit juice has exceptional antibacterial, antifungal, and antiviral capabilities [19]. In Japan, experiments on mice showed that tumor growth stopped after mice were being injected under the skin with grapefruit extract.…”
Section: Grapefruit (Citrus Paradisi)mentioning
confidence: 99%
“…For example, surfactants are used to solubilize hydrophobic drugs, methylcellulose can be used to prepare drug suspensions or added to tablets as a disintegrating agent, and cyclodextrin can be used to improve drug stability or control drug release [ 5 ]. However, not all PEs are “inactive”, and some are reported to affect the activity of metabolic enzymes, such as cytochrome P450 (CYP450) 3A4/5 (CYP3A4/5), CYP2C9, CYP2C19, CYP2D6, CYP2E1, CYP1A2, and UGT1A1 [ 6 , 7 , 8 , 9 , 10 ], or drug transporters, such as P-gp, BCRP, MRP2, and OATP1A2/2B1 [ 11 , 12 , 13 , 14 ]. For example, Martin and colleagues investigated the impact of 23 commonly used excipients (10 polymers and 13 surfactants) on CYP2E1, CYP3A4, CYP3A5, CYP2C9, CYP2C19, CYP1A2, and CYP2D6 using baculosome-derived CYP450 enzymes across a range of concentrations [ 10 ].…”
Section: Introductionmentioning
confidence: 99%